1998
DOI: 10.1590/s0034-89101998000400006
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes de trabalho em Barcelona (Espanha), no período de 1992-1993

Abstract: INTRODUÇÃO: As estatísticas dos acidentes de trabalho, como qualquer outro sistema de notificação, devem servir de base para determinar prioridades e decidir quais medidas preventivas devem ser adotadas. Neste contexto, o objetivo do estudo é aprofundar a análise dos acidentes de trabalho através da utilização de técnicas estatísticas descritivas que permitam estabelecer a relação entre o número de acidentes de trabalho ocorridos em Barcelona (Espanha) e as variáveis tipo de acidente, setor econômico, tamanho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
10

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 3 publications
2
4
0
10
Order By: Relevance
“…Accordingly, effective experience may be less in the temporary workers. This finding of higher accident risk of the temporary workers is similar to the experience of some already published reports 14,15) , which have dealt with accidents of temporary workers. The cause of this increased risk can be attributed to some factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, effective experience may be less in the temporary workers. This finding of higher accident risk of the temporary workers is similar to the experience of some already published reports 14,15) , which have dealt with accidents of temporary workers. The cause of this increased risk can be attributed to some factors.…”
Section: Discussionsupporting
confidence: 90%
“…Some epidemiological investigations 14,15) have highlighted the role of job security in injury causation. These studies have shown that the temporary workers are more vulnerable to occupational injuries than permanent workers.…”
mentioning
confidence: 99%
“…This finding of higher accident risk of the temporary piece rated workers is similar to the experience of some already published reports 21,23) which have dealt with accidents of temporary workers. The cause of this increased risk can be attributed to some factors.…”
Section: Discussionsupporting
confidence: 89%
“…Work conditions 5) , age [6][7][8][9] , educational status, safety training 10) , experience 11) , smoking 12,13) , alcohol [14][15][16][17] , psychosocial factors 18) , shift of work 19) and weather 20) have all been designated as responsible factors. Some authors have also shown that the type of worker (temporary or permanent) 21) and speed of work 22) are also important factors in the causation of occupational accidents. Some epidemiological investigations 21,23) have shown that the temporary workers are more vulnerable to occupational accidents than permanent workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation